FORMULA ANALYSIS OF SOCCER THEMED MOVIES: A STUDY OF CONVENTION AND INVENTION IN POPULAR LITERATURE - Neisya, Neisya; Yanti, Cita Hikmah (Universitas Muhammadiyah Palembang, 2019)
This study aims to analyze the narrative structure or formula in several soccer-themed movies; namely Garuda di Dadaku, Shaolin Soccer, Bend it Like Beckham, Barefoot Dreams, and Air Bud 3: World Pup. The writers try to see the convention in the entire movies and show up the invention that makes the movie different from each other. In analyzing, the writers use the descriptive method and structuralism theory as the approach of popular literature. The result shows that there are six conventions; the introduction of the main character that have problems, the main character’s initiative to solve problems, the problem is slightly solved, the suspense of success, the increasingly complex problem in the climax, and happy ending. Meanwhile, the inventions contained in the movies are more about culture. The producers try to combine this ball theme with a culture that is prevalent in the community so that it feels more familiar with the audience being the target market.